Unmixing for ultra-high-plex fluorescence imaging - Archibald Enninful; Alev Baysoy; Rong Fan (Nature Communications, 2022)
Writing in Nature communications, Seo and collaborators presented PICASSO as a method to achieve 15-color imaging of spatially overlapping proteins using no reference emission spectra in a single staining and imaging round. This accessible tool has the potential to be applied to diverse applications within the spatial biology field without neglecting accuracy.